PENGARUH PERUBAHAN NILAI KURS RUPIAH, SUKU BUNGA SBI DAN INFLASI TERHADAP INDEKS HARGA SAHAM GABUNGAN PADA TAHUN 2013-2016 - Ulfa Ilmiyatis Sholichah; Maslichah Maslichah; Muhammad Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTStock trading in Indonesia currently has progressed very rapidly. This canhappen because the progress of information technology has helped a lot intransactions in the capital market. In investment, high inflation causes investorsto be more careful in selecting and conducting transactions, so investors tend towait to invest until the economic conditions are conducive to avoiding the risksthat may be caused by high inflation. The purpose of the study was to analyze theeffect of the Rupiah Exchange Rate, SBI Interest Rate and Inflation on theComposite Stock Price Index (CSPI) on the Indonesia Stock Exchange in 2013-2016. To analyze the influence of the Rupiah / USD Exchange Rate on theComposite Stock Price Index (CSPI) on the Indonesia Stock Exchange in 2013-2016. To analyze the effect of the Indonesian Bank Certificate (SBI) Interest Rateon the Composite Stock Price Index (IHSG) on the Indonesia Stock Exchange in2013-2016. To analyze the effect of inflation rates on the Composite Stock PriceIndex (CSPI) on the Indonesia Stock Exchange in 2013-2016. Based onsimultaneous testing (together) it can be seen that the independent variablesincluding the Rupiah Exchange Rate, SBI Interest Rate, and Inflation, have apositive effect on the Composite Stock Price Index on the Indonesia StockExchange in 2013-2016. The value of the Rupiah Exchange has a significantnegative effect on the Composite Stock Price Index on the Indonesia StockExchange in 2013-2016. SBI Interest Rate has a significant positive effect on theComposite Stock Price Index on the Indonesia Stock Exchange in 2013-2016.Inflation has a significant positive effect on the Composite Stock Price Index onthe Indonesia Stock Exchange in 2013-2016.Keywords: Value of Rupiah Exchange Rate, SBI Interest Rate, Inflation,Composite Stock Price Index (CSPI)